Inventing the "Great Awakening" - Lambert, Frank (Princeton Univ. Press, 1999)
This book is a history of an astounding transatlantic phenomenon, a popular evangelical revival known in America as the first Great Awakening (1735-1745). Beginning in the mid-1730s, supporters and opponents of the revival commented on the extraordinary nature of what one observer called the "great ado," with its extemporaneous outdoor preaching, newspaper publicity, and rallies of up to 20,000 participants. Frank Lambert, biographer of Great Awakening leader George Whitefield, offers an overview of this important episode and proposes a new explanation of its origins.